2011
DOI: 10.1186/1743-422x-8-235
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of duck enteritis virus UL53 gene and glycoprotein K

Abstract: BackgroundMost of the previous research work had focused on the epidemiology and prevention of duck enteritis virus (DEV). Whilst with the development of protocols in molecular biology, nowadays more and more information about the genes of DEV was reported. But little information about DEV UL53 gene and glycoprotein K(gK) was known except our reported data.ResultsIn our paper, the fluorescent quantitative real-time PCR(FQ-RT-PCR) assay and nucleic acid inhibition test were used to study the transcription chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…To identify the DEV UL41 gene type, we studied its transcription and expression kinetics at different time points post-infection using RT-qPCR and western blot analysis, respectively. Based on previous studies [ 32 , 37 , 48 , 49 ], we suggested that accumulation of the DEV pUL41 may occur during the late stage of infection. IE genes are expressed in the presence of CHX, a protein synthesis inhibitor, while transcription of E and L genes is suppressed in the presence of CHX [ 50 ].…”
Section: Discussionmentioning
confidence: 84%
“…To identify the DEV UL41 gene type, we studied its transcription and expression kinetics at different time points post-infection using RT-qPCR and western blot analysis, respectively. Based on previous studies [ 32 , 37 , 48 , 49 ], we suggested that accumulation of the DEV pUL41 may occur during the late stage of infection. IE genes are expressed in the presence of CHX, a protein synthesis inhibitor, while transcription of E and L genes is suppressed in the presence of CHX [ 50 ].…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, generation of MP may be closely associated with the initiation of apoptosis and necrosis (Ardoin et al, 2007). Whether stress-inducible proteins, such as hypoxia-inducible factor 1α (HIF-1α), heat-shock factor (HSF-1), heat-shock protein (Hsp) family, nuclear factor κB (NF-κB), Jun NH2-terminal kinase (JNK), and p53 (Ohiro et al, 2003; Razorenova et al, 2005; Thompson and Locarnini, 2007; Zinkernagel et al, 2007; De Maio, 2011; Li et al, 2011; Rawat and Mitra, 2011; Zhang et al, 2011) and MHC class I polypeptide-related sequence A and B (MICA, MICB; Stern-Ginossar and Mandelboim, 2009) are involved, remains to be determined. Nevertheless, a broad array of pro-inflammatory cytokines, such as tumor necrosis factor (TNF), interleukin-1 (IL-1), IL-6, and type 1 interferons (IFN-I) are produced in response to infection (Medzhitov and Horng, 2009), and many of these induce MP shedding in the absence of infection (Combes et al, 1999; Sheremata et al, 2006; Penet et al, 2008).…”
Section: Mp In Inflammatory Conditionsmentioning
confidence: 99%
“…The characteristics of some genes from DEV had been reported [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. However, the function of VP16 of duck enteritis virus encoded by the UL48 gene was hardly studied.…”
Section: Introductionmentioning
confidence: 99%